2004
DOI: 10.1007/s00438-003-0964-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of defense-responsive genes in bacterial blight resistance of rice mediated by the recessive R gene xa13

Abstract: Defense responses triggered by dominant and recessive disease resistance (R) genes are presumed to be regulated by different molecular mechanisms. In order to characterize the genes activated in defense responses against bacterial blight mediated by the recessive R gene xa13, two pathogen-induced subtraction cDNA libraries were constructed using the resistant rice line IRBB13--which carries xa13--and its susceptible, near-isogenic, parental line IR24. Clustering analysis of expressed sequence tags (ESTs) ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 64 publications
(62 reference statements)
1
26
0
Order By: Relevance
“…This hypothesis is consistent with the moderate to high heritability previously reported for damage from MLD within E. globulus (narrow-sense heritability ¼ 0.12-0.60; Dungey et al 1997;Milgate et al 2005b). However, the possibility that the regions with QTL of large effect represent clusters of closely linked genes cannot be dismissed since resistance genes are commonly clustered in plants (Wang et al 2001;Chu et al 2004;Mondragon-Palomino and Gaut 2005). Due to the lack of QTL studies for disease resistance in Eucalyptus, comparative mapping is not possible.…”
Section: Discussionsupporting
confidence: 87%
“…This hypothesis is consistent with the moderate to high heritability previously reported for damage from MLD within E. globulus (narrow-sense heritability ¼ 0.12-0.60; Dungey et al 1997;Milgate et al 2005b). However, the possibility that the regions with QTL of large effect represent clusters of closely linked genes cannot be dismissed since resistance genes are commonly clustered in plants (Wang et al 2001;Chu et al 2004;Mondragon-Palomino and Gaut 2005). Due to the lack of QTL studies for disease resistance in Eucalyptus, comparative mapping is not possible.…”
Section: Discussionsupporting
confidence: 87%
“…Here, we used a previously discovered variant of avrXa7 (avrXa7-sacB50) that elicits resistance in IR24 and derived near-isogenic lines to compare the PXO99 A reaction to a typical HR on rice (22). Gene-profiling experiments with xa13 have also noted atypical defense gene expression profiles in IRBB13 plants after challenge with incompatible bacteria (25). Here, we demonstrated that the defense-related peroxidase gene PXO22.3 was not elevated in IRBB13 after challenge with PXO99 A .…”
Section: Discussionmentioning
confidence: 84%
“…RNA was extracted and 20 g of total RNA was used for RNA gel blot analysis as described previously (Chu et al 2004) using the same 782-bp probe as for DNA gel blot analysis. The other hybridization probes were cDNA clones BI145L12 (GenBank accession no.…”
Section: Dna Gel Blot and Rna Expression Analysesmentioning
confidence: 99%